A comparison of three bioenergy production systems using lifecycle assessment - Hassan, Zakia (SLU/Dept. of Forest Products, 2009)
Fossil fuel contributes to global warming through emissions of greenhouse gases such as CO2. Measures to reduce these gases may affect food security due to the productive land allocated for bioenergy production. The aim of this study was to show how leguminous tree species can contribute to the sustainability and economy of bioenergy production systems on degraded land. Specific objectives were; firstly, to describe how energy is produced by Eucalyptuspellets, Sesbania-pellets and sugarcane-ethanol systems through out the life cycle (LCA), and secondly, analysis of emission reduction by these bioenergy systems. The empirical background data used consists of data collected from different reports and investigations. The studied reports cover a broad range of site conditions and methodological approaches. As the analysis was based on secondary data, an inventory was carried out for energy input and output, emission and uptake of CO2 from all stages in the life cycle of the assessed products. It is interesting in this study to have incredible bioenergy production yet it is difficult to obtain enough consistent data. However, it reveals some remarkable outcomes that can guide future research. Such outcomes included the high potential for sustainable bioenergy production on degraded land by using improved fallow with Sesbania which reduces the energy input, costs and emissions from using commercial N-fertilizers.